Understanding Financial Management Practices in Sociological Perspectives: A Transcendental Phenomenological Study - La ode sumail; Salma Abdullah; Hisnol Jamali (Entrepreneurship and Small Business Research, 2022)
The purpose of this study is to uncover financial management practices from a sociological perspective. Conventional finance focuses only on materials or assets, which seem to have no spirit or social oxygen, even though those spirits have an important role in financial governance. This study used transcendental phenomenological methodology. A total of five key informants were involved in the study. All the key informants involved have at least ten years of experience as banana traders "Epe" on the Losari beach of Makassar City. This research found that the harmonization between the heart and the rational is supplied by new benefits of social oxygen that create new spirits and new energy in the form of social and economic. So that it has the potential to provide the best financial governance (excellent value) to other companies, in addition to the company's internals, the company will become dazzling and have the potential to produce the best performance (always the best) and sustainable growth. So it is not an exaggeration that excellent value, charm, always the best, and sustainable growth are characteristics of humanist financial management that are not found in conventional financial management.